The Effect of Theraband Exercises on Motor Performance and Swimming Degree of Young Swimmers - Zait Burak Aktuğ; Şeyda Nur Vural; Serkan İbiş (Selcuk University, 2019)
Different training methods are used to improve children's swimming degrees and motor performance. There are a limited number of studies examining the effects of therabands, which are portable and available everywhere, on swimmers. The aim of this study was to investigate the effect of 8 weeks of theraband exercises on motor performance and 50 m freestyle swimming degree. 45 voluntary children (male = 27, female = 18) participated in the study. The children were divided into three groups; control group (CG), swimming group (SG) and theraband group (TG), each consisting of 15 people. SG did swimming training only three times a week for eight weeks. In addition to swimming exercises, TG did theraband exercises consisting of 8 movements to the lower and upper extremities. The motor performances of the swimmers were determined by the Dordel Koch Test (DKT), which consists of 7 subtests, and swimming degrees were determined by the stopwatch. Wilcoxon Signed Ranks Test was used to determine the difference between pre-tests and post-tests following 8-weeks of exercise. According to the results, it was determined that in SG, 50 m swimming degree and DKTsideward jump performances increased in the posttest, while in TG, 50 m swimming degree, DKTsideward jump, DKTflexibility, DKT standing long jump, DKTsit-up, DKTbalance and DKTpush-up performances improved significantly in the post-test (p lt;0.05). As a result, in addition to in-water training to improve swimming performance, it can be stated that land training has positive effects on swimming degrees and theraband exercises increase motor performance. It can be recommended that swimming coaches incorporate theraband exercises into the content of training programs to improve both swimming and motor performance of children.